2020
DOI: 10.1016/j.apsb.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine-based drug delivery towards tumor biological and immunological microenvironment

Abstract: The complex tumor microenvironment is a most important factor in cancer development. The biological microenvironment is composed of a variety of barriers including the extracellular matrix and associated cells such as endothelia cells, pericytes, and cancer-associated fibroblasts. Different strategies can be utilized to enhance nanoparticle-based drug delivery and distribution into tumor tissues addressing the extracellular matrix or cellular components. In addition to the biological microenvironment, the immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 226 publications
(242 reference statements)
0
47
0
Order By: Relevance
“…This strategy can allow an understanding of differential cell uptake of nanomedicines, as exemplified by a study from Costa et al, who studied the uptake of chitosan-histidine-arginine nanoparticles encapsulating plasmid (p)DNA in a 2D co-culture of MCF7 cells and human fibroblasts [67] . Nanomedicines that modulate the TME generally target stromal cells, given their role in cancer cell growth and spread, or activate immune cells to then target cancer cells [68] . As a prime example, Zanganeh et al proposed the use of Ferumoxytol®, an FDA-approved iron oxide nanoparticle, as a means to prevent breast cancer hepatic metastasis and potentiate TAM-associated immunotherapy for breast cancer [69] .…”
Section: Selecting In Vitro Breast Cancer Models For Nanomedicine Developmentmentioning
confidence: 99%
“…This strategy can allow an understanding of differential cell uptake of nanomedicines, as exemplified by a study from Costa et al, who studied the uptake of chitosan-histidine-arginine nanoparticles encapsulating plasmid (p)DNA in a 2D co-culture of MCF7 cells and human fibroblasts [67] . Nanomedicines that modulate the TME generally target stromal cells, given their role in cancer cell growth and spread, or activate immune cells to then target cancer cells [68] . As a prime example, Zanganeh et al proposed the use of Ferumoxytol®, an FDA-approved iron oxide nanoparticle, as a means to prevent breast cancer hepatic metastasis and potentiate TAM-associated immunotherapy for breast cancer [69] .…”
Section: Selecting In Vitro Breast Cancer Models For Nanomedicine Developmentmentioning
confidence: 99%
“…Current research shows that tumors might escape immune surveillance via PD-1/PD-L1 axis upon NPPA-PTX NPs chemotherapy (Peng et al, 2015;Yang et al, 2020) which highlights the significance of combining the chemotherapeutic agent NPPA-PTX NPs with immune checkpoint blockade molecules like aPD-L1. In addition, it was known that 'hot' tumors are T cell-inflamed and highly immunogenic which are usually good responders to immune checkpoint inhibitors (Li & Burgess, 2020). Besides, the higher level of TNF-a and IFN-c in serum and tumor tissues of combination therapy indicated that NPPA-PTX NPs induced NK cell proliferation, and stimulated TNF-a and IFN-c production (Jewett et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…NPs possess several advantages for drug delivery due to their small size that allow their penetration into small capillaries and result in efficient accumulation at the target sites 28 , 29 , 30 . After intravenous administration, the conventional NPs are taken-up by the monocytes and macrophages of the reticuloendothelial system (RES) and rapidly cleared from the bloodstream, thereby limiting therapeutic effects 31 , 32 .…”
Section: Np-based Dds For Ambmentioning
confidence: 99%